Serological status for BTV‐8 in French cattle prior to the 2015 re‐emergence. Issue 1 (22nd September 2017) - Courtejoie, N.; Durand, B.; Bréard, E.; Sailleau, C.; Vitour, D.; Zientara, S.; Gorlier, A.; Baurier, F.; Gourmelen, C.; Benoit, F.; Achour, H.; Milard, C.; et al.
Summary: Undetected in Europe since 2010, bluetongue virus serotype 8 (BTV‐8) re‐emerged in August 2015 in Central France. To gain insight into the re‐emergence on the French territory, we estimated the seroprevalence in cattle before the detection of BTV‐8 in 2015, in areas differentially affected by the current outbreak. A retrospective survey based on the analysis of stored sera was thus conducted in the winter preceding the re‐emergence in seven French departments including the one where the virus was first detected. A total of 10, 066 sera were retrieved from animals sampled in 444 different herds in winter 2014/15. Between‐herd seroprevalence revealed the presence of seropositive animals in almost all herds sampled (97.4%). The animal‐level seroprevalence averaged at 44%, with a strong age pattern reflecting the cumulative exposure to both natural infection and to vaccination. A multivariable analysis allowed separating the respective effects of both exposures. A higher proportion of seropositivity risk was attributed to vaccination (67.4%) than to exposure to natural infection (24.2%). The evolution of seroprevalence induced by the two main risk factors in 74 mainland departments was reconstructed between the vaccination ban (2013) and the re‐emergence (2015). We showed a striking decrease in seroprevalence with time after the vaccination ban, due to population renewal, which could have facilitated virus transmission leading to the current outbreak situation.